Vitrification of Bovine Embryos: Can it Replace Slow Freezing? - Doultani, Shilpa; Layek, S S; R, Sudharson; Karuppanasamy, K; Patil, S P; Raval, K B; George, L B; Highland, Hyacinth (Animal Reproduction Update, 2025)
The ability to effectively cryopreserve embryos plays a critical role in assisted  reproductive technologies (ART) by facilitating the global exchange of valuable  genetics and minimizing disease transmission risks. However, a key challenge lies  in ensuring the post-thaw viability of cryopreserved embryos, particularly in vitro produced (IVP) embryos, which exhibit lower cryotolerance than their in vivo  counterparts. This study assessed the suitability of vitrification as an alternative to  the slow freezing method for cryopreservation of bovine IVP embryos. The research  compared the effectiveness of vitrification using high-security vitrification (HSV)  straws, a closed system, with two different slow-freezing protocols (0.3°C/min and  0.5°C/min). Blastocyst and expanded blastocyst stage embryos produced through  ovum pick-up (OPU) and in vitro embryo production were subjected to each  cryopreservation method and then thawed and cultured to assess their viability, re expansion, and hatching rates. The vitrified group demonstrated significantly higher  hatching rates (47.7%) than both slow freezing groups (10.6% for 0.5°C/min and  26.4% for 0.3°C/min). While vitrification resulted in higher viability and expansion  rates than the 0.5°C/min slow freezing group, it was higher in the 0.3°C/min group  in both parameters. Hatching from the zona pellucida is a prerequisite for successful  implantation, and the hatching rate was higher in the vitrified embryos, indicating a  potential advantage in terms of implantation readiness. These findings suggest that  vitrification may offer higher pregnancy rates as indicated by higher hatching rates.  The results may be further validated through embryo transfer studies to assess its  impact on actual pregnancy success rates.
Keywords: Bovine embryo cryopreservation; high-security vitrification (HSV) straws; slow freezing; vitrification